Pequi peel meal in laying hen diet - Amanda Lapa Silva; Romênia Regina Pires Lage; Daniel Emygdio de Faria Filho; Izabela Lorena Azevedo; Adélio Nunes Dias; Douglas Emygdio de Faria (Acta Scientiarum. Animal Sciences, 2016)
This study evaluated the effect of pequi peel meal in the diet for laying hens on performance and egg quality. Hy-Line® Brown hens (n=160) aged 55 weeks with 1642±63g body weight were distributed in a completely randomized design with five treatments and four replications of eight birds each. The treatments consisted of isometric substitution of corn by pequi peel meal at 0, 2.5, 5.0, 7.5 and 10%. The performance and internal and external egg quality were evaluated. Egg production, egg mass and feed conversion worsened linearly with increasing replacement of corn with pequi peel meal, while the yolk color increased linearly. The other variables related to performance and internal and external egg quality were not significantly affected by the treatments. It can be concluded that the use of pequi peel meal replacing corn in laying hen diet does not change the internal and external egg quality, improves the pigmentation of egg yolk, and impairs performance of laying hens.